Is EarthCheck community standard an effective sustainable tourism management tool? : a case study on Snæfellsnes Peninsula, Iceland - Church, Lindsay (2011)
The Westfjords Tourism Board decided to work towards gaining EarthCheck community standard in the Westfjords, Iceland in 2010. This sparked the researcher to determine if this international environmental community standard is more than just an eco-label. The research goals determined if gaining EarthCheck community certification improved the environmental, economic and social well-being in Snæfellsnes; if EarthCheck certification was an effective sustainable tourism marketing tool; and, how the Westfjords could learn from the Snæfellsnes case with respect to applying for EarthCheck certification and applying effective destination management. This single explanatory-exploratory case study revealed through two site visits, seven EarthCheck documents and thirteen semi-structured interviews a number of interesting results analyzed using a SWOT analysis. Strengths of the EarthCheck community standard programme in Snæfellsnes included a number of spin-offs such as schools gaining the Green Flag and marinas being awarded the Blue Flag. Lack of public participation, partnership, integration and clarity are considered pivotal weaknesses discussed. An opportunity identified was the capacity of the EarthCheck certification to encourage an integrated environmental planning approach among multiple communities. Major threats were the cost of implementing the EarthCheck programme and the long-term timeline needed to attain success. The environment impacts in Snæfellsnes as a result of gaining EarthCheck community certification were overall positive and an overall change in environmental thinking among residents did occur which is believed to be in response to the EarthCheck programme. The local Snæfellsnes economy was not enhanced because of EarthCheck however; improving the local economy is not a main goal of the EarthCheck programme. Currently the EarthCheck certification has yet to be used as a marketing tool to draw tourists to the region so it was not possible to successfully address the second research goal. Lastly, a ...